2020
DOI: 10.2478/auseb-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Ease of Doing Business: Evidence from ECOWAS

Abstract: Corruption has a major impact on growth in low-income economies, while ease of doing business has a major impact on growth in developed countries. The study empirically examines the effect of corruption on ease of doing business. The study analyses unbalanced panel data of corruption rank, corruption score, control of corruption, and inflation, together with other economic and financial institutional factors and ease of doing business score for the period of 2004–2017. Results indicate that: corruption rank, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The result is consistent with previous studies, which show that easiness in doing business perceived to be happened in ''cleaner'' countries. (Mongay & Filipescu, 2012;Nageri & Gunu, 2020). Second, this study reveals that economic growth, as shown by GDP per capita, is indeed linked with CPI scores.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The result is consistent with previous studies, which show that easiness in doing business perceived to be happened in ''cleaner'' countries. (Mongay & Filipescu, 2012;Nageri & Gunu, 2020). Second, this study reveals that economic growth, as shown by GDP per capita, is indeed linked with CPI scores.…”
Section: Discussionmentioning
confidence: 53%
“…In the context of more specific countries and more recent studies, Nageri & Gunu (2020) found that control of corruption scores positively impacts doing business in West African countries using multiple regression analysis. The result supports the finding by Mongay & Filipescu (2012).…”
Section: Eodb and Cpi: Are These Two Related?mentioning
confidence: 95%
“…In fact, either the possibility of attracting FDI, either the ability to help the population to take charge of the business risk, also depends on regulations that are in favour of risk takers and that do not get the debtors excessively if they are entrepreneurs. Corruption, inflation, and imports are negatively associated to EDB in a set of countries in the period 2014-2017 for West African Countries (Nageri & Gunu, 2020). The regulatory policy is an essential tool to promote EDB in India (Natarajan & Raza, 2017) and Oman (Bhandari & Mohite, 2022).…”
Section: Edb and Governancementioning
confidence: 99%
“…In fact, either the possibility of attracting FDI, either the ability to help the population to take charge of the business risk, also depends on regulations that are in favour of risk takers and that do not get the debtors excessively if they are entrepreneurs. Corruption, inflation, and imports are negatively associated to EDB in a set of countries in the period 2014-2017 for West African Countries [12]. The regulatory policy is an essential tool to promote EDB in India [13] and Oman [14].…”
Section: Edb and Fdimentioning
confidence: 99%